Xanthogranulomatous pyelonephritis, and emphysematous pyelonephritis: Two rare conditions in one patient. (September 2021) - Mhmed Ali, Rihan; Haidar, Mariam
Abstract: Introduction: What makes this case unique are combined features of two rare renal disease processes in one patient within one kidney which are Xanthogranulomatous pyelonephritis, and emphysematous pyelonephritis. Case presentation: The patient had main general symptoms like fever, chills, fatigue, and right abdominal pain. He had urea = 77, White Blood Cells = 15, 46, and urine culture was positive for Klebsiella. He had right total nephrectomy as a therapeutic intervention. Conclusion: It is important to note that it could we have two diseases or more in one case related to one systemic organ so, we have to evaluate all possible causes of current status of the patient. Highlights: Xanthogranulomatous pyelonephritis is a distinct uncommon variant of chronic pyelonephritis. Emphysematous pyelonephritis is also a rare condition. The main cause of xanthogranulomatous pyelonephritis is Escherichia coli followed by proteus organisms. The main treatment for both conditions is total nephrectomy.